2013
DOI: 10.1126/scitranslmed.3006516
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Effector Memory T Cell–Based Mucosal and Systemic Immunity with Pulmonary Nanoparticle Vaccination

Abstract: Many pathogens infiltrate the body and initiate infection via mucosal surfaces. Hence, eliciting cellular immune responses at mucosal portals of entry is of great interest for vaccine development against mucosal pathogens. We describe a pulmonary vaccination strategy combining Toll-like receptor (TLR) agonists with antigen-carrying lipid nanocapsules [interbilayer-crosslinked multilamellar vesicles (ICMVs)], which elicit high-frequency, long-lived, antigen-specific effector memory T cell responses at multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
138
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 41 publications
1
138
0
1
Order By: Relevance
“…However, elastic particles (e.g., liposomes) that may deform during transport appear to have different size limits (25). Virus-like particles (VLPs), based on self-assembling proteins (26)(27)(28) and synthetic polymer or lipid nanoparticle formulations (21,(29)(30)(31)(32), have been demonstrated to enhance vaccine accumulation in LNs and to promote superior cellular and humoral immunity to a variety of antigens in mice relative to soluble forms of protein and peptide vaccines. In addition to size, particle surface chemistry plays a key role in lymphatic trafficking by regulating the tendency toward aggregation in physiological conditions and interactions with cells and/or ECM.…”
Section: Codelivery Of Antigen and Danger Signalsmentioning
confidence: 99%
“…However, elastic particles (e.g., liposomes) that may deform during transport appear to have different size limits (25). Virus-like particles (VLPs), based on self-assembling proteins (26)(27)(28) and synthetic polymer or lipid nanoparticle formulations (21,(29)(30)(31)(32), have been demonstrated to enhance vaccine accumulation in LNs and to promote superior cellular and humoral immunity to a variety of antigens in mice relative to soluble forms of protein and peptide vaccines. In addition to size, particle surface chemistry plays a key role in lymphatic trafficking by regulating the tendency toward aggregation in physiological conditions and interactions with cells and/or ECM.…”
Section: Codelivery Of Antigen and Danger Signalsmentioning
confidence: 99%
“…Induction of long-lasting CTLs with subunit vaccines requires, first, delivery of antigen to cross-presenting dendritic cells (DCs) and, second, potent activation of these DCs by the vaccine adjuvant, which instructs DCs how to activate T cells. Nanocarriers can be used to modulate the immune response induced by antigens and adjuvants by modifying their characteristics, such as stability, tissue and cell targeting, and DC-activating capacity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We have previously described the targeting benefits of conjugating antigens to ultrasmall Pluronic-stabilized poly(propylene sulfide) (PPS) nanoparticles (NPs) in terms of CD8 + T-cell and Th1 responses (13,14).…”
mentioning
confidence: 99%
“…163 This imprinting ability of lung DCs was confirmed in humans, as it was shown that CD1c lung DCs co-cultured with CD8 + T cells promote upregulation of CD103 and CD49a on these cells. 164 Other studies support the role of mucosal immunity in protecting against mucosal tumors.…”
mentioning
confidence: 77%